(untitled) (Journal of Laboratory Animal Science, 2024)
The aim of the present study was to investigate the hepatoprotective and antioxidant activity of Momordica charantia in cow urine on streptozotocin-induced diabetic rats. The alcoholic extract of Momordica charantia was administered orally in cow urine at 200 mg/kg body weight to diabetic rats and the results were compared with standard antidiabetic drug, glinbenclamide. The results showed that there was a significant (P<0.001) increase in serum glucose, AST, ALT, cholesterol, triglyceride levels and significant (P<0.001) reduction in liver SOD, GPx and CAT activity indicating liver damage in diabetic control rats. The biochemical analysis was well supported by histopathological evaluation of the liver which showed necrosis and vacuolar degeneration of hepatocytes in diabetic rats. Oral administration of Momordica charantia in cow urine gradually and progressively improved the clinical condition of the diabetic rats. There was significant (P≤0.001) reduction in the serum AST, ALT, cholesterol and triglycerides levels. The treatment also resulted in the significant (P≤0.001) increase in reduced SOD, GPx and CAT activity in the liver of diabetic rats. Histopathology revealed a progressive improvement in the architecture and return to normalcy of hepatocytes. The results clearly suggested that fruit extract of Momordica charantia in cow urine at 200 mg/kg body weight may effectively normalize the hepatic damage and impaired antioxidant status in STZ-induced diabetic rat sthan glibenclamide treated groups.